Landscape in Middle English Romance: The Medieval Imagination and the Natural World - Richmond, Andrew M. (Cambridge studies in medieval literature, 2021)
"In Sir Isumbras, one of the most enduringly popular late medieval romances, the penitential experience of its eponymous hero (modeled off of the evergreen St. Eustace tales) is grounded in a careful exploration of hillside ironmines and the communities of smiths that rely upon them. Such an interest in natural resource management and industrial development derives from the notable focus on charting topography that distinguishes the central third of the romance - marking Isumbras's transition from secular to divine systems of values, and his geographical movement from Christian to Saracen lands. Similarly, in the fourteenth-century Middle English version of William of Palerne (hereafter William), the eponymous protagonist flees with his lover, Melior, through a world of forests and bays that overflows with topographical details. These intricate explanations of quarry pits, hollow oaks, roadside groves, seaside caves, and war-torn estates together compose a perspective on landscape defined by networks of economic exchange. In this regard, the predominant view of the natural world presented in William ties it to earlier romances such as Havelok the Dane, a text interested in the systems of exchange that knit seaside fishermen to urban markets; and to later texts such as the Middle English versions of Partonope of Blois, which demonstrates in its depictions of estates the mercantile and agricultural uses of natural spaces that underlie the successful maintenance of a noble identity. This chapter, then, will discuss how Middle English romances' attention to the management and harvest of natural resources often reveals the link between country and urban spaces created by the exchange of such goods. I will also consider how sympathetic portrayals of laborers and other low-class harvesters of natural resources suggest that romances, particularly around the turn of the fifteenth century, reflect the shifting nature of their bourgeois-gentry audience by engaging with the environmental experiences of merchants, household clerks, reeves, franklins, and gentry farmers in addition to those of the higher aristocracy"--
Keywords: History and criticism; English literature; History and criticism; Landscapes in literature; Seashore in literature; Middle English, 1100-1500; Romances, English; SCSU Faculty Scholar Award; award_winner; dept.eng